CT and MR Imaging of the Encephalopathic Child - Warner, HM; Batty, R.; Hart, AR; Mordekar, SR; Raghavan, A.; Williams, F; Connolly, DJA (Current Medical Imaging, 2018)
Background: Neonatal and paediatric encephalopathy can be a diagnostic challenge for clinicians. Potential aetiologies include hypoxic brain injury, stroke, infection, trauma, metabolic and electrolyte abnormalities, autoimmune conditions and drug ingestion. Radiology plays a key role in determining aetiology and, even when normal, directing further assessment. Conclusion: We present a review of the neuroradiological manifestations of neonatal and paediatric encephalopathies which will aide paediatricians and radiologists in their assessment of children with this condition.
Keywords: paediatric neuroimaging